Jiwa Puitis Nenek Moyang Orang Buton dalam Mendirikan Rumah Tradisional Buton Malige di Kota Baubau - Umar, Muhammad Zakaria; Faslih, Arman; Rosyidah, Sitti (RUAS (Review of Urbanism and Architectural Studies), 2018)
Our ancestors were poetic in architecture. This study was aimed at studying the ancient poets ancestral spirits against traditional Buton malige houses. This research used architectural criticism method. The model of interpretive criticism with variant advocatory criticism is used in architectural criticism model. This study concluded that the ancestors of the Buton people were poetic in making the traditional Buton malige house. The ancestral spirit of the Buton people against the malige building takes place in the talk of the macro cosmos-cosmic cosmos and the principles of Islamic teachings of Tasawuf transformed into talks of floor plans, looks, and pieces.